Estudo sobre a compensação de processos integradores com atraso e a proposição de uma nova abordagem - Mazzini, Humberto Mendes (2003)
The compensation of process with time delays has been of interest to academics and pratitioners for several decades. Additionally, proportional integral derivative (PID) controllers are widely used in the process industries. The simplicity and the ability of these controllers to solve most practical control problems have greatly contributed to this wide acceptance. However, they may not provide satisfactory closed loop responses when the process considered is either a high-order plant or a plant with a long dead time. In these cases a powerful technique, the Smith predictor, can be used. However, these regulators cannot reject load disturbance for processes with integration. A review of the literature for compensation methods of process with time delay and Smith predictor (and its modifications) is presented. The focus of the thesis is subsenquently broadened with the consideration of compensation methods for integrating process and the proposition of a new approach. The proposed method for PID (or its variations) controllers is based on the specification of the desired closed loop transfer function for disturbances. Although the approach is designed for disturbance rejection, the set-point responses are usually satisfactory and can be independently tuned. Simulation examples show the simplicity and better robustness of the proposed method over previously published approaches both for the set-point response and for the load disturbance rejection.